2018
DOI: 10.1002/jsfa.9118
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐harvest factors related to sensory profile of Passiflora setacea nectars, a wild passion fruit from Brazilian savannah

Abstract: Passiflora setacea nectar is a potential functional beverage, due its bioactive contents. Training system and season had no influence on acceptance as isolated factors. However, there was an interaction between these factors, which could be considered to market projection, as well as the addition of seeds. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
2
1
Order By: Relevance
“…Passion fruit showed the best bioactive composition. Previous studies reported a lower (0.761-5.442 mg gallic acid equivalent g −1 ) (CARVALHO et al, 2018) or higher (342.80-382.00 mg gallic acid equivalent L −1 ) (DEVI RAMAIyA et al, 2013) total polyphenol concentration than in the present research.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Passion fruit showed the best bioactive composition. Previous studies reported a lower (0.761-5.442 mg gallic acid equivalent g −1 ) (CARVALHO et al, 2018) or higher (342.80-382.00 mg gallic acid equivalent L −1 ) (DEVI RAMAIyA et al, 2013) total polyphenol concentration than in the present research.…”
Section: Resultscontrasting
confidence: 86%
“…Pineapple and passion fruit showed a ph and total acidity (Table 4) similar to other studies (CARVAlhO et al, 2018;gERMER et al, 2017). The physicochemical characterization of yacon showed a higher ph, but a low soluble solid content.…”
Section: Physicochemical Characterization Of Mixed Juicesupporting
confidence: 84%
“…De Carvalho et al 33 used consumer tests to evaluate passion fruit nectar, and reported that the most common descriptors were 'characteristic of fresh fruit’, ‘color’, and ‘acid taste’ – that is, the characteristics of fresh fruit were expected in the product. In this research, although descriptors related to the flavor and color of the tamarind fruit were also important for the acceptance of the functional tamarind beverage, the descriptor ‘refreshment sensation’ emerged as a new characteristic that should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a ratio close to 1 indicates a relatively low predominance of one over the other, favouring the development of a final product with a more balanced flavour. It must be pointed that a higher concentration of fruit pulp may influence in the reduction of the TSS/ TTA ratio, for fruit are considered as sources of acids, mainly citric acid (de Carvalho et al 2018). For example, Formulation 2 had a higher fruit pulp content than Formulation 1 (640 g vs 360 g), which resulted in a higher TTA (14.30 g/100 mL vs 10.30 g/100 mL) and a lower TSS/TTA ratio (1.84 vs 2.77).…”
Section: Physicochemical Analysesmentioning
confidence: 99%